2004
DOI: 10.4315/0362-028x-67.6.1271
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection of Bacillus and Staphylococcus in Various Foods

Abstract: A broad-range PCR assay for the detection of bacteria belonging to Bacillus and Staphylococcus genera was developed. Primers targeting the bacterial 16S rRNA gene were newly designed and used in a PCR assay. To determine the specificity of the assay, 81 different bacterial strains (of 50 genera), 2 fungi, 3 animals, and 4 plants were tested. Results were positive for every tested Bacillus, Staphylococcus, or Aerococcus strain. In addition, the result for Listeria grayi was positive with lower PCR product. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Various methods have been described in the literature for DNA extraction from foods for real-time PCR, since it is highly sensitive towards inhibitory substances originating from the food matrix (32). Often these methods include a complexing step (e.g., cetyltrimethylammonium bromide), magnetic beads, or commercially available kits (33,40,41), but also simple methods like boiling have been reported to be suitable (10). In this study, two commercially available kits (see Materials and Methods) and a simple boiling method were used for DNA isolation from artificially contaminated foods to evaluate the robustness of the real-time assays.…”
Section: Resultsmentioning
confidence: 99%
“…Various methods have been described in the literature for DNA extraction from foods for real-time PCR, since it is highly sensitive towards inhibitory substances originating from the food matrix (32). Often these methods include a complexing step (e.g., cetyltrimethylammonium bromide), magnetic beads, or commercially available kits (33,40,41), but also simple methods like boiling have been reported to be suitable (10). In this study, two commercially available kits (see Materials and Methods) and a simple boiling method were used for DNA isolation from artificially contaminated foods to evaluate the robustness of the real-time assays.…”
Section: Resultsmentioning
confidence: 99%
“…The foods involved in outbreaks are canned, smoked and salted products, frozen Wshery products, boiled Wsh paste and Wsh sausages which inhibit the growth of competing organisms (Bryan, 1980;Nakano et al, 2004;Sanjeev, Iyer, Rao, & James, 1986). Freshly caught seafoods are free from S. aureus and contamination takes place upon handling (Bryan, 1980;Shewan, 1962).…”
Section: Introductionmentioning
confidence: 98%
“…The study found that the PCR assay detected the bacteria, during the inoculation (S. aureus) of 10À90 CFU/g into noodle foods containing endogenous microflora (10 3 to 10 5 CFU/g) followed by a 6-h enrichment culture step. [23] PCR is a powerful technology, but the limitations of the PCR amplification technique include difficulty in obtaining a DNA preparation suitable for PCR amplification and the procedures are rather complicated with Figure 1. Schematic diagram of polymerase chain reaction.…”
Section: Polymerase Chain Reaction Detectionmentioning
confidence: 99%
“…http://orcid.org/0000-0003-1491-7808 Simple, rapid, sensitive, and specific detection of poisoning of enterotoxins [15] Immunomagnetic separation (IMS) method 40 min 1.5£10 3 (in PBS) and 1.5£10 5 CFU (in milk sample) for S. aureus Easy, convenient, and rapid sensing method for a wide range of pathogens [17] Conventional PCR method 8.5 h 10 to 90 CFU/g into noodle foods containing by a 6-h enrichment culture step Difficulty in obtaining a DNA preparation, procedures are rather complicated, clean environment [23] Real-time fluorescence quantitative PCR 1.5À3 h 1.5 £ 10 2 to 6.4 £ 10 2 copies of the nuc gene/2 g in cheese matrix…”
Section: Xihong Zhaomentioning
confidence: 99%